PERENCANAAN STRATEGIS GUNA PENGEMBANGAN WISATA DAN PRODUK LOKAL DESA BANSARI - Ihsan Mochamad Chairul; Indika Deru R (COMVICE: Journal Of Community Service, 2023)
This program aims to maximize the economic potential of Bansari Village through strategic planning for tourism and local product development. The first stage involves mapping out the potential, challenges, and introduction of Bansari Village's flagship products, which include sectors such as agriculture, plantations, and tourism. The village is rich in flagship products like Premium Melon and chili that have been exported abroad, as well as having the Embung Bansari tourist attraction. However, there are obstacles in utilizing digital platforms for marketing and the management of the Village-Owned Enterprise (BUMDes) which is not yet well-structured. The second stage focuses on assisting the village to improve BUMDes management capabilities, including the implementation of Business Model Canvas workshops, financial reporting, and the use of information technology. The final stage involves evaluation and interactive discussions to address the problems faced. These activities result in concrete strategies for the management and promotion of tourism and local products, which are expected to enhance the welfare of the Bansari Village community